Policies for expanding family planning coverage: lessons from five successful countries - Hellwig, Franciele; Moreira, Laísa Rodrigues; Silveira, Mariângela F.; Vieira, Carolina Sales; Rios-Quituizaca, Paulina Belén; Masabanda, Marcela; Serucaca, Joel; Rudasingwa, Silas; Nyandwi, Alypio; Mulu, Shegaw; Rashad, Hoda; Barros, Aluísio J. D. (Frontiers in Public Health, 2024)
Background: Enhancing the design of family planning interventions is crucial for promoting gender equality and improving maternal and child health outcomes. We identified, critically appraised, and synthesized policies and strategies from five selected countries that successfully increased family planning coverage. Methods: We conducted a policy analysis through a scoping review and document search, focusing on documents published from 1950 to 2023 that examined or assessed policies aimed at enhancing family planning coverage in Brazil, Ecuador, Egypt, Ethiopia, and Rwanda. A search was conducted through PubMed, SCOPUS, and Web of Science. Government documents and conference proceedings were also critically analyzed. National health surveys were analyzed to estimate time trends in demand for family planning satisfied by modern methods (mDFPS) at the national level and by wealth. Changes in the method mix were also assessed. The findings of the studies were presented in a narrative synthesis. Findings: We selected 231 studies, in which 196 policies were identified. All countries started to endorse family planning in the 1960s, with the number of identified policies ranging between 21 in Ecuador and 52 in Ethiopia. Most of the policies exclusively targeted women and were related to supplying contraceptives and enhancing the quality of the services. Little focus was found on monitoring and evaluation of the policies implemented. Conclusion: Among the five selected countries, a multitude of actions were happening simultaneously, each with its own vigor and enthusiasm. Our findings highlight that these five countries were successful in increasing family planning coverage by implementing broader multi-sectoral policies and considering the diverse needs of the population, as well as the specific contextual factors at play. Successful policies require a nuanced consideration of how these policies align with each culture's framework, recognizing that both sociocultural norms and the impact of past public policies shape the current state of family planning.